Genome sequence of Theileria parva, a bovine pathogen that transforms lymphocytes - Gardner, M.J.; Bishop, Richard P.; Shah, Tushaar; Villiers, Etienne P. de; Carlton, J.M.; Hall, N.; Ren, Q.; Paulsen, I.T.; Pain, A.; Berriman, M.; Wilson, R.J.M.; Sato, S.; et al. (American Association for the Advancement of Science, 2005)
We report the genome sequence of Theileria parva, an apicomplexan pathogen causing economic losses to smallholder farmers in Africa. The parasite chromosomes exhibit limited conservation of gene synteny with Plasmodium falciparum, and its plastid-like genome represents the first example where all apicoplast genes are encoded on one DNA strand. We tentatively identify proteins that facilitate parasite segregation during host cell cytokinesis and contribute to persistent infection of transformed host cells. Several biosynthetic pathways are incomplete or absent, suggesting substantial metabolic dependence on the host cell. One protein family that may generate parasite antigenic diversity is not telomere-associated.